The concept and legal nature of personal non-property rights of spouses in family law doctrine - Parfentiev, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The scientific article researches the concept and legal nature of personal non-property rights of spouses in the family law doctrine. In particular, the author notes in the article that the personal non-property rights of spouses are, on the one hand, relations regulated by the norms of family law regarding the personal non-property goods and interests of married persons, on the other hand, they are subjective, natural, those that cannot be transferred to another person, inalienable rights of an immaterial, long-lasting nature that arise and operate from the moment of marriage and are changed or terminated from the moment of dissolution of marriage, namely from the date of registration of the dissolution of marriage, or from the date of entry into force of the court decision on dissolution of marriage. The author defines the following list of signs of personal non-property rights of spouses: they arise from the moment of marriage, registered in the state registration bodies of acts of civil status; are decisive in family relations compared to property relations – other rights of spouses arise from them as derivatives; exercise of these rights is possible subject to agreement with the other spouse and taking into account the interests of the family as a whole; arise in connection with the conclusion of a marriage and can be terminated only in the event of the death of one of the spouses or dissolution of the marriage, recognition of the marriage as invalid, cannot be terminated or changed by agreement of the spouses, and cannot be exhausted as a result of their implementation; the list of personal non-property rights of spouses is determined by national culture, historical traditions, socio-economic conditions, and personal factors; do not have an economic meaning and are not of a property nature; arising from certain intangible assets; closely related to the personality of each of the spouses, inseparable from it and cannot be alienated, just like the goods themselves, in connection with which personal non-property rights and obligations arise; cannot be the subject of a marriage contract; timelessness; exercise of rights in accordance with the moral principles of society; saturation with norms of a moral nature; their inexhaustibility by those rights defined in family legislation.